Examining the Legal Foundations of Political Party Liability for Money Laundering - Fitriyana, Lolita; Firmansyah, Ridho (Universitas Airlangga, 2026)
Political parties serve as platforms for individuals before they are nominated for state office. State officials, in turn, carry a significant risk of engaging in corrupt practices. However, to date, there has been no case in Indonesia in which a corruption offense committed by a state official who is also part of a political party’s leadership has resulted in the political party itself being held criminally liable. Given the frequency of such incidents, this study seeks to contribute to law-enforcement efforts to prevent and address this issue, particularly when political parties benefit from the unlawful actions of their members or officials. In addition to a statutory approach, this research adopts conceptual and case-based analyses to reinforce its findings. The results indicate that, as legal entities, political parties can indeed be held criminally liable.